Analysis of wind climate and wind energy potential of regions in Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Investments in wind plants have increased rapidly as a result of changes to legal regulations in Turkey over the last five years. This has also led to an increase in the number of wind potential analyses in various regions of the country. This study analyzes the wind climate features of three regions in Turkey and their energy potential. In order to determine the features of wind in these regions, a five-layer Sugeno-type ANFIS model established under the MATLAB-Simulink software was used and the relationship between wind speed and other climate variables determined. In the second phase, WASP software was used to complete the wind energy potential analyses using wind speed data. The final phase includes calculations of the amount of electricity to be obtained technically and capacity usage rates of the installed turbines if wind farms are established in the selected areas. The comparative tables and graphics of the said areas were obtained. In conclusion, the selected areas are well located for the installation of parallel-connected wind plants to the national network in terms of the reliability of wind, the dispersion of wind potential and capacity usage rates. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; ANFIS; WASP; Sugeno; Energy potential analysis; ANFIS